Integrating SFL and Visual Grammar in Genre-Based Pedagogy to Foster EFL Students’ Critical Reading of Multimodal Texts - Emiliasari, Raynesa Noor; Emilia, Emi; Hermawan, Budi (Universitas Muhammadiyah Malang, 2025)
This research aims to integrate Linguistic Functional Systems (SFL) and Visual Grammar in genre-based pedagogy to encourage EFL students' critical reading of multimodal texts. The main problem raised in this study is the lack of students' understanding of multimodal texts, often found in English as a foreign language (EFL) education. The main objective of this study was to explore how incorporating SFL and visual grammar can improve students' critical reading abilities of the text. The method used is a qualitative approach with a case study design that involves multimodal text analysis, classroom observation, and interviews with teachers and students. The research data was obtained through direct observation of learning interactions in the EFL classroom, multimodal text analysis, and student responses regarding the learning. The results show that the integration of SFL and visual grammar is effective in enriching students' understanding of structure and meaning in multimodal texts, as well as improving their critical skills. The conclusions of this study confirm that a genre-based pedagogical approach that combines SFL and visual grammar can strengthen students' critical reading, making them better prepared to understand and analyze multimodal texts in greater depth.